(untitled) (Fiep Bulletin - online, 2015)
Introduction: This paper has analyzed the possibility to insert Pilates Methodology into Physical Education (PE) classes in Public Elementary Teaching in order to contribute to school community promoting the development of the body culture movement. The paper has arisen from the necessity to assist students totally so that they can feel reinserted into society as true citizens. The Objective was to verify the possibility to include Pilates Ground Method in the PE classes and to contribute with the activities that can meet students’ educational needs in a total way. Methodology: This study was based on bibliographic and documental methodology, on the laws that regulate that students have the right to education and also on the teaching experience of the author, on teaching activities, research and extension in public elementary and high school teaching. Results and discussion: The analysis of the method was based on construction process, and the reality of research interpretation was based on bibliographic and documental review like: The Constitution, (1988); Leis de Diretrizes e Bases da EducaçãoNacional,(LDBEN, 1996); Basic Curriculum of Elementary Teaching in the State of Goiás; Cruz,(2013); Minayo,(1996); Moura, (2009); Pilates, (2010); Filho& Garcia,(2012); among others. Conclusion: It is of utmost relevance to insert Pilates’ ground method into thePhysical Education classes, thus,ensuring fairness to students, since this practice will also be able to develop them as social beings so that they can become individuals who can act in diverse fields of society in a democratic way and ones who can participate rationally in this change.